A UV-proof fabric
By applying an anti-ultraviolet emulsion on the fabric, using hydrophobic modified mesoporous silica and nanosilver anti-ultraviolet agents, as well as cinnamaldehyde and other antibacterial sustained-release agents, the fabric is not protected under ultraviolet light and has poor anti-bacterial properties, and the fabric is efficiently protected against ultraviolet and long-term antibacterial effects.
Patent Information
- Application Number
- CN202410035400.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
When existing fabrics are exposed to ultraviolet light for a long time, it is difficult to effectively protect human skin, and their antibacterial properties are insufficient.
The anti-UV emulsion including polyurethane emulsion, anti-UV agent and anti-bacterial sustained-release agent is coated on the surface of the fabric body. The anti-UV agent consists of hydrophobic modified mesoporous silica and nanosilver, and the anti-bacterial sustained-release agent consists of cinnamaldehyde, colloidal wall material and crosslinking agent.
It significantly improves the UV resistance and long-term antibacterial properties of the fabric, and can maintain high UV resistance and antibacterial effects after multiple washes.
Smart Images

Figure BDA0004657519100000071 
Figure BDA0004657519100000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fabrics, and in particular to an anti-ultraviolet fabric. Background Art
[0002] Fabrics are materials used to make clothing, etc. Fabrics can not only interpret the style and characteristics of clothing, but also directly influence the color and shape of clothing.
[0003] Polyester fabric is a commonly used chemical fiber clothing fabric in clothing. It is wrinkle-resistant and very suitable for outerwear as well as various outdoor products such as bags and tents. Ultraviolet rays are electromagnetic waves with a frequency between visible light and X-rays. The main source of ultraviolet rays in nature is the sun. However, prolonged exposure to ultraviolet light can be harmful to human skin. Therefore, it is necessary to develop an anti-UV fabric. Summary of the invention
[0004] In order to improve the anti-ultraviolet performance of fabrics, the present application provides an anti-ultraviolet fabric.
[0005] The present application provides an anti-ultraviolet fabric adopting the following technical solution: The invention comprises a fabric body and an anti-ultraviolet coating, wherein the anti-ultraviolet coating is obtained by coating an anti-ultraviolet emulsion on the surface of the fabric body, and the anti-ultraviolet emulsion comprises the following components in parts by weight: 180-220 parts of a polyurethane emulsion, 17-23 parts of an anti-ultraviolet agent, 12-16 parts of an antibacterial sustained-release agent, and 5-7 parts of a dispersant; the anti-ultraviolet agent comprises hydrophobically modified mesoporous silica and nano-silver.
[0006] By adopting the above technical scheme, the anti-ultraviolet emulsion is coated on the surface of the fabric body, so that the anti-ultraviolet coating is attached to the surface of the fabric body, thereby improving the anti-ultraviolet performance of the fabric body; nanosilver is loaded into the hydrophobically modified mesoporous silica, which can synergistically absorb ultraviolet rays and reduce the ultraviolet rays passing through the fabric body, thereby improving the anti-ultraviolet performance of the fabric body; at the same time, an antibacterial sustained-release agent is added to the anti-ultraviolet emulsion, and the antibacterial sustained-release agent and nanosilver can synergistically inhibit bacteria and play a long-term antibacterial role, thereby improving the long-term antibacterial performance of the fabric.
[0007] Preferably, the hydrophobically modified mesoporous silica comprises isopropoxy tris(ethylenediamino-N-ethoxy) titanate and mesoporous silica.
[0008] By adopting the above technical scheme, mesoporous silica is modified by isopropoxy tris(ethylenediamino-N-ethoxy) titanate, so that titanate is grafted to the surface of mesoporous silica. On the one hand, the dispersion performance of mesoporous silica can be improved to reduce the agglomeration phenomenon of mesoporous silica, thereby improving the stability of nano-silica. On the other hand, the modified mesoporous silica can further improve the contact angle of the anti-ultraviolet coating, thereby improving the overall water washability of the fabric.
[0009] Preferably, the mass ratio of the isopropoxy tris(ethylenediamino-N-ethoxy) titanate to the mesoporous silica is (0.02-0.04):1.
[0010] By adopting the above technical scheme and controlling isopropoxy tris(ethylenediamino-N-ethoxy) titanate and mesoporous silica, an anti-ultraviolet agent with excellent performance can be obtained.
[0011] Preferably, the hydrophobically modified mesoporous silica is prepared by the following method: The mesoporous silica is vacuum dried and mixed with toluene. After ultrasonic oscillation, isopropoxy tris(ethylenediamino-N-ethoxy) titanate is added. After ultrasonic oscillation, the temperature is raised and stirred to react to obtain a prefabricated solution. The prefabricated solution is centrifuged to remove the supernatant to obtain a reaction solid. The reaction solid is dispersed in tert-butanol and ultrasonically oscillated to remove residual isopropoxy tris(ethylenediamino-N-ethoxy) titanate to obtain hydrophobically modified mesoporous silica.
[0012] Preferably, the antibacterial sustained-release agent comprises a colloid wall material, cinnamaldehyde and a cross-linking agent.
[0013] By adopting the above technical scheme, cinnamaldehyde is used as a core material and coated into a colloidal wall material to prepare an antibacterial sustained-release agent. Cinnamaldehyde is an aldehyde organic compound with bactericidal, disinfectant and antiseptic properties. After cinnamaldehyde is released from the colloidal wall material, it can effectively improve the overall antibacterial properties of the fabric. The cinnamaldehyde released from the colloidal wall material synergistically inhibits bacteria with nano-silver particles, thereby effectively improving the overall antibacterial properties of the fabric.
[0014] Preferably, the mass ratio of the colloid wall material, cinnamaldehyde and cross-linking agent is 1:2:(0.18-0.12).
[0015] By adopting the above technical solution and controlling the colloid wall, cinnamaldehyde and cross-linking agent within the above range, the overall performance of the antibacterial sustained-release agent can be improved.
[0016] Preferably, the antibacterial sustained-release agent is prepared by the following method: Tannic acid is dispersed in deionized water to obtain a tannic acid solution, a colloidal wall material is mixed with deionized water to obtain a prefabricated wall material solution, cinnamaldehyde is added to the prefabricated wall material solution, stirred and then subjected to shear treatment, the pH value is adjusted to 4-5 to obtain a preliminary product of a sustained-release agent, the preliminary product of the sustained-release agent is subjected to an ice bath treatment while maintaining stirring conditions, the tannic acid solution is added, stirred and then separated, and the product after removing the liquid is freeze-dried to obtain an antibacterial sustained-release agent.
[0017] Preferably, the gelatinous wall material comprises gelatin and gum arabic.
[0018] Gelatin and gum arabic are used together as wall materials to coat the core material. Gelatin and gum arabic are sticky and can fill into the tiny pores and uneven surfaces in the fabric fibers, thereby improving the stability between the antibacterial sustained-release agent and the fabric body.
[0019] Preferably, the cross-linking agent is tannic acid.
[0020] By adopting the above technical solution, tannic acid also has good antibacterial properties, and the phenolic hydroxyl groups in tannic acid can form strong hydrogen bonds with the proteins in the colloid wall material, thereby improving the overall stability of the antibacterial sustained-release agent.
[0021] Preferably, the dispersant is one or more of hexenyl bisstearamide, tristearic acid glyceryl or stearic acid monoglyceride.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. The surface of the fabric body is coated with an anti-ultraviolet emulsion to make the fabric have good anti-ultraviolet performance. The hydrophobically modified mesoporous silica of the anti-ultraviolet agent has good anti-ultraviolet performance, and nanosilver also has excellent ultraviolet resistance. The combination of the two can further improve the anti-ultraviolet performance of the anti-ultraviolet agent. Nanosilver is loaded into the hydrophobically modified mesoporous silica, which can make the nanosilver slowly released, thereby playing a long-term anti-ultraviolet effect, further improving the time of the anti-ultraviolet performance of the fabric; 2. An antibacterial sustained-release agent is also added to the anti-ultraviolet agent, and cinnamaldehyde is coated in a colloid wall material. Gelatin and gum arabic are used as wall materials, which can make the antibacterial sustained-release agent better adhere to the surface of the fabric fiber, thereby improving the stability of the antibacterial sustained-release agent; after a period of time, cinnamaldehyde is released from the wall material. Cinnamaldehyde has anti-ultraviolet and antibacterial properties, so as to improve the long-term antibacterial and anti-ultraviolet performance of the fabric body. DETAILED DESCRIPTION
[0023] The present application discloses an anti-ultraviolet fabric, and the present application is further described in detail below in conjunction with the embodiments: In the embodiment of the present application, the fabric body is selected to be polyester fabric.
[0024] Mesoporous silica was purchased from Bohuasi Nanotechnology (Ningbo) Co., Ltd.
[0025] Example 1 Preparation of UV protection agent: After 30 g of mesoporous silica was vacuum dried for 2 hours, it was placed in a four-necked flask, and then 150 mL of toluene was added, and ultrasonic oscillation was performed at a temperature of 50°C for 30 minutes. Then, 1.2 mL of isopropoxy tris(ethylenediamino-N-ethoxy) titanate (CAS No.: 65380-84-9) was added. After ultrasonic oscillation for 30 minutes, the temperature was raised to 70°C, and the reaction was stirred at a speed of 200 rpm for 4 hours to obtain a prefabricated solution. The prefabricated solution was centrifuged at a speed of 1000 / min for 45 minutes, and the supernatant was removed to obtain a reaction solid. The reaction was fixed and dispersed in 100 mL of tert-butanol, and ultrasonic oscillation was performed to remove the residual isopropoxy tris(ethylenediamino-N-ethoxy) titanate to obtain hydrophobically modified mesoporous silica.
[0026] A silver nitrate solution with a concentration of 0.002 mol / L and a sodium borohydride solution with a concentration of 0.005 mol / L were prepared; 25 g of the hydrophobically modified mesoporous silica prepared above was mixed with 1000 mL of ethanol, and ultrasonically dispersed for 90 minutes to obtain a standby mesoporous silica ethanol solution, and 500 mL of the silver nitrate solution prepared above was added to the standby mesoporous silica ethanol solution, and the reaction was shielded from light for 3.5 hours at 25°C to obtain a reaction preparatory solution; 25 g of polyvinyl pyrrolidone was dispersed in 1000 mL of deionized water to obtain a polyvinyl pyrrolidone dispersion, and the polyvinyl pyrrolidone dispersion was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, stirred for 2 hours, and then 200 mL of the sodium borohydride solution was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, and after centrifugation, deionized water and ethanol were used to wash alternately for 3 times, and freeze-dried at -4°C for 12 hours to obtain an anti-ultraviolet agent.
[0027] Preparation of antibacterial sustained-release agent: Weigh 3.07 g of gelatin and 3.42 g of gum arabic to obtain a colloid wall material; disperse 50 g of tannic acid (CAS No.: 1401-55-4) in 500 mL of deionized water to obtain a tannic acid solution; add the colloid wall material to 100 mL of deionized water, stir to obtain a wall material pre-solution; add 12.99 g of cinnamaldehyde (CAS No.: 104-55-2) to the wall material pre-solution, stir at 200 rpm for 5 min at 50 ° C, and then heat with a high temperature. The mixture was sheared at a speed of 8000 r / min for 5 min in a speed disperser, the temperature was maintained at 50°C, and stirring was continued at a speed of 200 rpm. Acetic acid was used to adjust the pH value to 4.5 to obtain a preliminary sustained-release agent. The preliminary sustained-release agent was treated in an ice bath for 1 h, and stirring was maintained. 5.2 mL of tannic acid solution was added, and stirring was carried out at a speed of 300 r / min for 5 h at 25°C. Subsequently, the mixture was allowed to stand for separation at 4°C, and the product after removing the liquid was freeze-dried at -4°C to obtain an antibacterial sustained-release agent.
[0028] Preparation of UV-resistant emulsion: Weigh 90 g of polyurethane emulsion, 17 g of the anti-ultraviolet agent prepared above, 12 g of the antibacterial sustained-release agent prepared above, and 5 g of dispersant, mix them, maintain the temperature at 45° C., and stir at a speed of 200 rpm for 5 min to obtain an anti-ultraviolet emulsion; Wherein, the dispersant is vinyl bisstearamide (CAS No.: 110-30-5).
[0029] To prepare fabrics with UV protection: The fabric body is completely immersed in the anti-ultraviolet emulsion prepared above, and the fabric body is taken out after keeping it for 30 minutes. Both sides of the fabric body are attached with the anti-ultraviolet emulsion. The fabric body is kept ventilated and dried for 2 hours to obtain the anti-ultraviolet fabric.
[0030] Example 2 Preparation of UV protection agent: 40 g of mesoporous silica was vacuum dried for 2 h and placed in a four-necked flask, followed by the addition of 150 mL of toluene and ultrasonic oscillation at 50 ° C for 30 min, followed by the addition of 1.6 mL of isopropoxy tris(ethylenediamino-N-ethoxy) titanate. After ultrasonic oscillation for 30 min, the temperature was raised to 70 ° C and stirred at 200 rpm for 4 h to obtain a prefabricated solution. The prefabricated solution was centrifuged at 1000 / min for 45 min, and the supernatant was removed to obtain a reaction solid. The reaction was fixed and dispersed in 100 mL of tert-butanol and ultrasonically oscillated to remove the residual isopropoxy tris(ethylenediamino-N-ethoxy) titanate to obtain hydrophobically modified mesoporous silica.
[0031] A silver nitrate solution with a concentration of 0.004 mol / L and a sodium borohydride solution with a concentration of 0.009 mol / L were prepared; 35 g of the hydrophobically modified mesoporous silica prepared above was mixed with 1000 mL of ethanol, and ultrasonically dispersed for 90 minutes to obtain a standby mesoporous silica ethanol solution, and 500 mL of the silver nitrate solution prepared above was added to the standby mesoporous silica ethanol solution, and the reaction was shielded from light for 3.5 hours at 25°C to obtain a reaction preparatory solution; 35 g of polyvinyl pyrrolidone was dispersed in 1000 mL of deionized water to obtain a polyvinyl pyrrolidone dispersion, and the polyvinyl pyrrolidone dispersion was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, stirred for 2 hours, and then 200 mL of the sodium borohydride solution was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, and after centrifugation, deionized water and ethanol were used to wash alternately for 3 times, and freeze-dried at -4°C for 12 hours to obtain an anti-ultraviolet agent.
[0032] Preparation of antibacterial sustained-release agent: Weigh 4.32 g of gelatin and 3.93 g of gum arabic to obtain a gelatinous wall material; disperse 50 g of tannic acid in 500 mL of deionized water to obtain a tannic acid solution, add the gelatinous wall material into 100 mL of deionized water, stir to obtain a wall material pre-solution, add 16.51 g of cinnamaldehyde to the wall material pre-solution, stir at 200 rpm for 5 min at 50°C, then shear at 8000 r / min for 5 min using a high-speed disperser, maintain the temperature of 50°C, continue stirring at 200 rpm, use acetic acid to adjust the pH value to 4.5, obtain a preliminary product of a sustained-release agent, treat the preliminary product of the sustained-release agent in an ice bath for 1 h, maintain stirring conditions, add 12.4 mL of tannic acid solution, stir at 300 r / min for 5 h at 25°C, then stand and separate at 4°C, and freeze-dry the product after removing the liquid at -4°C to obtain an antibacterial sustained-release agent.
[0033] Preparation of UV-resistant emulsion: 220 g of polyurethane emulsion, 23 g of the above-prepared anti-ultraviolet agent, 16 g of the above-prepared antibacterial sustained-release agent and 7 g of dispersant were weighed and mixed, maintained at 45° C., and stirred at 200 rpm for 5 min to obtain an anti-ultraviolet emulsion.
[0034] To prepare fabrics with UV protection: The fabric body is completely immersed in the anti-ultraviolet emulsion prepared above, and the fabric body is taken out after keeping it for 30 minutes. The anti-ultraviolet emulsion is attached to both sides of the fabric body. The fabric body is kept ventilated and dried for 2 hours to obtain the anti-ultraviolet fabric; Wherein, the dispersant is glyceryl tristearate (CAS No.: 555-43-1).
[0035] Example 3 Preparation of UV protection agent: 35 g of mesoporous silica was vacuum dried for 2 hours and placed in a four-necked flask, followed by the addition of 150 mL of toluene and ultrasonic oscillation at 50°C for 30 minutes. Then, 1.05 mL of isopropoxy tris(ethylenediamino-N-ethoxy) titanate was added and ultrasonic oscillation was performed for 30 minutes. The temperature was raised to 70°C and stirred at 200 rpm for 4 hours to obtain a prefabricated solution. The prefabricated solution was centrifuged at 1000 / min for 45 minutes. The supernatant was removed to obtain a reaction solid. The reaction was fixed and dispersed in 100 mL of tert-butanol and ultrasonically oscillated to remove the residual isopropoxy tris(ethylenediamino-N-ethoxy) titanate to obtain hydrophobically modified mesoporous silica.
[0036] A silver nitrate solution with a concentration of 0.003 mol / L and a sodium borohydride solution with a concentration of 0.007 mol / L were prepared; 30 g of the hydrophobically modified mesoporous silica prepared above was mixed with 1000 mL of ethanol, and ultrasonically dispersed for 90 minutes to obtain a standby mesoporous silica ethanol solution, and 500 mL of the silver nitrate solution prepared above was added to the standby mesoporous silica ethanol solution, and the reaction was shielded from light for 3.5 hours at 25°C to obtain a reaction preparatory solution; 30 g of polyvinyl pyrrolidone was dispersed in 1000 mL of deionized water to obtain a polyvinyl pyrrolidone dispersion, and the polyvinyl pyrrolidone dispersion was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, stirred for 2 hours, and then 200 mL of the sodium borohydride solution was added dropwise to the reaction preparatory solution at a rate of 90 drops / min, and after centrifugation, deionized water and ethanol were used to wash alternately for 3 times, and freeze-dried at -4°C for 12 hours to obtain an anti-ultraviolet agent.
[0037] Preparation of antibacterial sustained-release agent: Weigh 3.68 g of gelatin and 3.68 g of gum arabic to obtain a gelatinous wall material; disperse 50 g of tannic acid in 500 mL of deionized water to obtain a tannic acid solution, add the gelatinous wall material into 100 mL of deionized water, stir to obtain a wall material pre-solution, add 14.74 g of cinnamaldehyde to the wall material pre-solution, stir at 200 rpm for 5 min at 50°C, then use a high-speed disperser to shear at 8000 r / min for 5 min, maintain the temperature of 50°C, continue stirring at 200 rpm, use acetic acid to adjust the pH value to 4.5, obtain a preliminary product of a sustained-release agent, treat the preliminary product of the sustained-release agent in an ice bath for 1 h, maintain stirring conditions, add 8.9 mL of tannic acid solution, stir at 300 r / min for 5 h at 25°C, then stand and separate at 4°C, and freeze-dry the product after removing the liquid at -4°C to obtain an antibacterial sustained-release agent.
[0038] Preparation of UV-resistant emulsion: 200 g of polyurethane emulsion, 20 g of the above-prepared anti-ultraviolet agent, 14 g of the above-prepared antibacterial sustained-release agent and 6 g of dispersant were weighed and mixed, maintained at 45° C., and stirred at 200 rpm for 5 min to obtain an anti-ultraviolet emulsion.
[0039] To prepare fabrics with UV protection: The fabric body is completely immersed in the anti-ultraviolet emulsion prepared above, and the fabric body is taken out after keeping it for 30 minutes. The anti-ultraviolet emulsion is attached to both sides of the fabric body. The fabric body is kept ventilated and dried for 2 hours to obtain the anti-ultraviolet fabric; Wherein, the dispersant is glyceryl monostearate (CAS No.: 123-94-4).
[0040] Example 4 Example 4 is based on Example 3, and the only difference between Example 4 and Example 3 is that in Example 4, when preparing mesoporous modified silica, 35 g of mesoporous silica is weighed, and 2.45 g of isopropoxy tris(ethylenediamino-N-ethoxy) titanate is weighed.
[0041] Example 5 Example 5 is based on Example 3, and the only difference between Example 5 and Example 3 is that when preparing mesoporous modified silica in Example 5, 35 g of mesoporous silica is weighed, and 0.35 g of isopropoxy tris(ethylenediamino-N-ethoxy) titanate is weighed.
[0042] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that when preparing the antibacterial sustained-release agent in Example 6, 15.13 g of cinnamaldehyde is weighed, when preparing the colloid wall material, 3.78 g of gelatin is weighed, 3.78 g of gum arabic is weighed, and 3 mL of tannic acid solution is added.
[0043] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that when preparing the antibacterial sustained-release agent in Example 7, 14.42 g of cinnamaldehyde is weighed, when preparing the colloid wall material, 3.61 g of gelatin is weighed, 3.61 g of gum arabic is weighed, and 13.7 mL of tannic acid solution is added.
[0044] Comparative Example 1 Comparative Example 1 is based on Example 3. The only difference between Comparative Example 1 and Example 3 is that when the anti-ultraviolet emulsion is prepared in Comparative Example 1, no anti-ultraviolet agent is added.
[0045] Comparative Example 2 Comparative Example 2 is based on Example 3. The only difference between Comparative Example 2 and Example 3 is that when the anti-ultraviolet emulsion is prepared in Comparative Example 2, no sustained release is added.
[0046] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the hydrophobically modified mesoporous silica is replaced by mesoporous silica.
[0047] Performance testing The fabrics of Examples 1-9 and Comparative Examples 1-4 were sampled and subjected to the following performance tests: (1) Anti-ultraviolet performance test According to GB / T 18830-2009 Evaluation of UV protection performance of textiles, the UV performance of the samples in the above examples was measured. Each sample was tested three times, and the results were filled in Table 1 after the test.
[0048] (2) Antibacterial performance test According to the standard of GB / T20944 Evaluation of Antibacterial Properties of Textiles, the antibacterial properties of the above samples were measured. Each sample was tested 3 times and the results were filled in Table 1 after the test. The tested bacteria were Escherichia coli ATCC25922 and Staphylococcus aureus ATCC6538.
[0049] (3) Washability test According to GB / T 5713-2013 Textiles - Tests for Colour Fastness to Water, the wash resistance of the above samples was tested. After washing 50 times, the UV inhibition rate was tested. Each sample was tested 3 times, and the results were filled in Table 1 after the test.
[0050] Table 1 Test results of fabric anti-ultraviolet, antibacterial and washability Performance test analysis As shown in Table 1, the ultraviolet antibacterial rates of the fabrics prepared in Examples 1-3 are all above 98%, indicating that the fabrics prepared in the present application have good anti-ultraviolet performance; the Escherichia coli inhibition rates of the fabrics prepared in Examples 1-3 are all above 99%, and the inhibition rates of Staphylococcus aureus are all above 99%, indicating that the fabrics prepared in the present application have good antibacterial performance; after washing 50 times, the anti-ultraviolet inhibition rates of Examples 1-3 are above 93%, indicating that the fabrics prepared in the present application have good water wash resistance; after 28 days, the inhibition rates of Escherichia coli are above 93%, and the inhibition rates of Staphylococcus aureus are above 93%, indicating that the present application has long-term antibacterial performance.
[0051] The performance of Example 4 and Example 5 is reduced. This is because the mass ratio of isopropoxy tris(ethylenediamino-N-ethoxy) titanate to mesoporous silica in Example 4 and Example 5 is outside the range specified in the present application. The anti-ultraviolet performance in Example 4 is reduced. This may be because the content of isopropoxy tris(ethylenediamino-N-ethoxy) titanate is too high, which affects the stability of the system, thus causing the performance of Example 4 to decline.
[0052] Too little isopropoxy tris(ethylenediamino-N-ethoxy) titanate is added in Example 5, so the modification effect on mesoporous silica is reduced, and the dispersibility of mesoporous silica in the emulsion system is reduced, resulting in agglomeration of some mesoporous silica. The overall stability of the emulsion system is reduced, so the UV resistance, antibacterial performance and water wash resistance in Example 5 are all reduced.
[0053] The antibacterial performance of Example 6 and Example 7 is reduced. This is because the mass ratio of cinnamaldehyde, colloidal wall material and tannic acid in Example 6 and Example 7 is outside the range specified in the present application. The antibacterial performance in Example 6 is reduced. This may be because the mass ratio of tannic acid is reduced, which makes the overall cross-linking degree of the antibacterial sustained-release agent lower, the tightness of the microcapsule structure is reduced, the particle size difference of the microcapsules is large, the stability of the system is reduced, and the bonding strength with the fabric fiber is reduced. At the same time, the cinnamaldehyde in the microcapsule is quickly released from the system and oxidized, and the long-term antibacterial effect is reduced; therefore, the antibacterial performance of Example 6 after washing is reduced.
[0054] In Example 7, the mass ratio of tannic acid is too large, which makes the density of the microcapsules too high, and the release rate of cinnamaldehyde from the microcapsules is too slow, making it difficult to effectively inhibit bacteria in a timely manner. Therefore, the antibacterial performance after water washing in Example 7 is reduced.
[0055] No anti-ultraviolet agent is added in Comparative Example 1, so the anti-ultraviolet performance of the fabric in Comparative Example 1 is reduced. At the same time, there are no nanosilver particles in Comparative Example 1, and the initial antibacterial effect is also reduced; no antibacterial sustained-release agent is added in Comparative Example 2, so it is difficult for Comparative Example 2 to achieve long-term antibacterial performance; in Comparative Example 3, the titanate-modified mesoporous silica is replaced with ordinary mesoporous silica, and no dispersant is added in Comparative Example 3, so the dispersion effect of each component in Comparative Example 3 is reduced, and the performance of each component in the anti-ultraviolet emulsion is also reduced; in Comparative Example 4, the titanate-modified mesoporous silica is replaced with ordinary mesoporous silica, and the anti-ultraviolet performance in Comparative Example 4 is reduced. This is because the mesoporous silica in Comparative Example 4 has not been modified, the dispersibility of the mesoporous silica in the emulsion system is reduced, the mesoporous silica is partially agglomerated, and the contact angle of the mesoporous silica that has not been modified with titanate is reduced, and the hydrophobicity is weakened, so the water washing resistance of Comparative Example 4 is also reduced.
[0056] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A UV-proof fabric, characterized in that: It includes a fabric body and an anti-ultraviolet coating, wherein the anti-ultraviolet coating is obtained by coating an anti-ultraviolet emulsion on the surface of the fabric body, and the anti-ultraviolet emulsion includes the following components in parts by weight: Polyurethane emulsion 180-220 parts 17-23 parts of anti-ultraviolet agent Antibacterial sustained-release agent 12-16 parts Dispersant 5-7 parts; The anti-ultraviolet agent comprises hydrophobically modified mesoporous silica and nano silver.
2. The anti-ultraviolet fabric according to claim 1, characterized in that: The hydrophobically modified mesoporous silica comprises isopropoxy tris(ethylenediamino-N-ethoxy) titanate and mesoporous silica.
3. The anti-ultraviolet fabric according to claim 2, characterized in that: The mass ratio between the isopropoxy tris(ethylenediamine-N-ethoxy) titanate and the mesoporous silica is (0.02-0.04):
1.
4. The anti-ultraviolet fabric according to claim 3, characterized in that: The hydrophobically modified mesoporous silica is prepared by the following method: The mesoporous silica is vacuum dried and mixed with toluene. After ultrasonic oscillation, isopropoxy tris(ethylenediamino-N-ethoxy) titanate is added. After ultrasonic oscillation, the temperature is raised and stirred to react to obtain a prefabricated solution. The prefabricated solution is centrifuged to remove the supernatant to obtain a reaction solid. The reaction solid is dispersed in tert-butanol and ultrasonically oscillated to remove residual isopropoxy tris(ethylenediamino-N-ethoxy) titanate to obtain hydrophobically modified mesoporous silica.
5. The anti-ultraviolet fabric according to claim 1, characterized in that: The antibacterial sustained-release agent comprises a colloid wall material, cinnamaldehyde and a cross-linking agent.
6. The anti-ultraviolet fabric according to claim 5, characterized in that: The mass ratio of the colloid wall material, cinnamaldehyde and cross-linking agent is 1:2:(0.18-0.12).
7. The anti-ultraviolet fabric according to claim 5, characterized in that: The antibacterial sustained-release agent is prepared by the following method: Tannic acid is dispersed in deionized water to obtain a tannic acid solution, a colloidal wall material is mixed with deionized water to obtain a prefabricated wall material solution, cinnamaldehyde is added to the prefabricated wall material solution, stirred and then subjected to shear treatment, the pH value is adjusted to 4-5 to obtain a preliminary product of a sustained-release agent, the preliminary product of the sustained-release agent is subjected to an ice bath treatment while maintaining stirring conditions, the tannic acid solution is added, stirred and then separated, and the product after removing the liquid is freeze-dried to obtain an antibacterial sustained-release agent.
8. The anti-ultraviolet fabric according to claim 6, characterized in that: The colloid wall material includes gelatin and gum arabic.
9. The anti-ultraviolet fabric according to claim 6, characterized in that: The cross-linking agent is tannic acid.
10. The UV-proof fabric according to claim 8, characterized in that: The dispersant is one or more of hexenyl bisstearamide, glyceryl tristearate or glyceryl monostearate.
Citation Information
Cited By
Preparation process of swimsuit fabric
CN120026501A